Relevansi Tradisi Buwuh dengan Pelestarian Nilai-Nilai Pendidikan Insani (Studi Kasus di Desa Bantrung Kecamatan Batealit Kabupaten) - Khoiriyyah, Fitriyyatul; Sukarman, Sukarman (Universitas Wahid Hasyim Semarang, 2023)
This research aims to examine the relevance of the buwuh tradition in Bantrung Village, Batealit District, Jepara Regency with the values of human education. This research is a type of qualitative field research with a case study approach. Data collection techniques in this research are observation, interviews and documentation. Data analysis is carried out by grouping, coding, reducing and presenting data in the form of descriptive analysis. The results of the research show that the buwuh tradition in Bantrung Village, Batealit District, Jepara Regency is a form of preserving culture and traditions that have been carried out from generation to generation. Meanwhile, the relevance of the buwuh tradition in Bantrung Village, Batealit District, Jepara Regency with the values of human education, includes: the values of tawazun (balance), justice, trustworthiness, honesty, ta'awun (mutual assistance), ukhuwah (brotherhood), and tasamuh (tolerance). The positive and negative impacts of the buwuh tradition in Bantrung Village, Batealit District, Jepara Regency with the values of human education, include: a) remembering God's blessings, b) helping each other by giving alms, emphasizing brotherly relationships, creating an attitude of helping each other, establishing harmonious relations between communities. Meanwhile, the negative impacts of the buwuh tradition include; burdening someone, being burdened with debt, returning buwuhan, problems in the economy.